Colchicine in the Treatment of Recurrent Oral Aphthous Ulcer -Open Clinical Trial in Bangladesh (Bangladesh Medical Journal, 2012)
Background: Recurrent aphthous Ulceration (RAU) is characterized by necrotizing ulcers of the oral mucosa that persist, remit, and recur for variable periods of time. Despite the benign nature of the disease, RAU frequently affects quality of life as a result of long lasting and recurrent episodes of burning pain.Aim and objective: the aim of the study was to determine the efficacy of colchicine in treatment of recurrent oral aphthous ulcer.Methods: A clinical trial was conducted among 30 samples in the department of dermatology and venereology of Bangabandhu Sheikh Mujib Medical University and Dhaka Medical College Hospital, Dhaka. Study was performed among those who fulfilled the inclusion criteria. Data was collected from 1st September 2007 to 29th February. 2008 and enrolled data was analyzed by using statistical SPSS win 13.Results: Among 30 patients, 24 (80%) were male and 6(20%) were female. Mean age of the patients was 26.20 (±6.65) years. 26(87.7%) patients found ulcer in oral mucosa and 4(13.3%)in tongue, but previous family history was present in only 20% cases out of 30 patients. All patients experienced a marked decrease in symptoms during colchicine treatment in where; mean aphthae count was 3.27 (±1.05) before treatment and 0.43 (±0.68) during treatment. Pain score also reduced during treatment from 6.80 (±2.12) to 1.13 (±.1.11) which was statistically highly significant.Conclusions: Colchicine may be a promising modality of treatment in the therapeutic armamentarium for RAU.DOI: http://dx.doi.org/10.3329/bmj.v39i3.9948 BMJ 2010; 39(3)